2018
DOI: 10.1007/s00125-017-4533-7
|View full text |Cite
|
Sign up to set email alerts
|

Bioelectronic modulation of carotid sinus nerve activity in the rat: a potential therapeutic approach for type 2 diabetes

Abstract: Aims/hypothesis A new class of treatments termed bioelectronic medicines are now emerging that aim to target individual nerve fibres or specific brain circuits in pathological conditions to repair lost function and reinstate a healthy balance. Carotid sinus nerve (CSN) denervation has been shown to improve glucose homeostasis in insulin-resistant and glucose-intolerant rats; however, these positive effects from surgery appear to diminish over time and are heavily caveated by the severe adverse effects associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
69
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(76 citation statements)
references
References 32 publications
7
69
0
Order By: Relevance
“…and insulin sensitivity were reversed after discontinuation of the electrical stimulus (44). Together, our results put in place the necessary tools to support a potential bioelectronic medicine-based therapeutic approach for Type 2 diabetes.…”
Section: Alternative Therapeutic Approachmentioning
confidence: 63%
See 1 more Smart Citation
“…and insulin sensitivity were reversed after discontinuation of the electrical stimulus (44). Together, our results put in place the necessary tools to support a potential bioelectronic medicine-based therapeutic approach for Type 2 diabetes.…”
Section: Alternative Therapeutic Approachmentioning
confidence: 63%
“…This approach would bring significant improvement in the standard of care for Type 2 diabetes, requiring minimally invasive procedures and negligible interference with daily activities (6,17). Along with this idea, we have recently demonstrated that the neuromodulation of CSN using kilohertz high frequency alternating current through cuff electrodes surgically placed on the CSN restores metabolic homeostasis in Type 2 diabetes rats (44). These beneficial effects of the neuromodulation of CSN activity on glucose homeostasis 3.…”
Section: Alternative Therapeutic Approachmentioning
confidence: 96%
“…; Sacramento et al . ). Knowing from our previous studies the importance of adenosine and ATP as key players in the chemotransduction at the CB, here we investigated the effect of ageing in key proteins involved in the purinergic metabolism in the CB and also the contribution of adenosine and ATP to the CB chemosensory activity.…”
Section: Introductionmentioning
confidence: 97%
“…More recently, Sacramento et al . () demonstrated that bilateral bioelectronic modulation of CSN activity restores insulin sensitivity and glucose tolerance in a rat model of type 2 diabetes suggesting that a bioelectronic medicine approach could bring significant advances to standard care for type 2 diabetes, providing long‐term glucose control and avoiding systemic effects. In this context and for safety purposes, studies are needed to find and refine therapeutic approaches that target the CB to reduce its activity and not to destroy it so that chemoreflex function is preserved.…”
mentioning
confidence: 99%
“…For example, Pijacka et al (2016) found that ATP acting via P2X3 receptors is responsible for the CB hyperactivity and hyperreflexia seen in essential hypertension, supporting the idea of the modulation of P2X3 receptors as a non-surgical strategy to control human hypertension. More recently, Sacramento et al (2018) demonstrated that bilateral bioelectronic modulation of CSN activity restores insulin sensitivity and glucose tolerance in a rat model of type 2 diabetes suggesting that a bioelectronic medicine approach could bring significant advances to standard care for type 2 diabetes, providing long-term glucose control and avoiding systemic effects. In this context and for safety purposes, studies are needed to find and refine therapeutic approaches that target the CB to reduce its activity and not to destroy it so that chemoreflex function is preserved.…”
mentioning
confidence: 99%